The contemporary relevance of John Dewey's theories on teaching and learning Deweyan perspectives on standardization, accountability, and assessment in education - Ávila, JuliAnna; Ring, Emer 1960-; Rud, A. G. 1953-; Waks, Leonard J. (Leonard Joseph) (Routledge international studies in the philosophy of education, 2022)
"Through expert analysis, this text proves that John Dewey's views on efficiency in education are as relevant as ever. By exploring Deweyan theories of teaching and learning, the volume illustrates how they can aid educators in navigating the theoretical and practical implications of accountability, standardization, and assessment. The Contemporary Relevance of John Dewey's Theories on Teaching and Learning deconstructs issues regarding accountability mechanisms, uniform assessment systems, and standardization processes through a Deweyan lens. Connecting the zeitgeist of the era from which Dewey's ideas emerged and current global political, social, and economic contexts, the book emphasizes the importance of resilient systems in reconciliating the tension between standardized assessments and individual student development. Contributors provide insights from a range of settings across Pre-K, primary, secondary, and higher education and address topics including teacher agency, voice, leadership, and democracy. The volume will be of interest to scholars, researchers, and academics with an interest in philosophy of education, education policy and the impact of neoliberal agendas, as well as teaching and learning more broadly"--